2010
DOI: 10.1073/pnas.0909364107
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer peptide PNC-27 adopts an HDM-2-binding conformation and kills cancer cells by binding to HDM-2 in their membranes

Abstract: The anticancer peptide PNC-27, which contains an HDM-2-binding domain corresponding to residues 12-26 of p53 and a transmembrane-penetrating domain, has been found to kill cancer cells (but not normal cells) by inducing membranolysis. We find that our previously determined 3D structure of the p53 residues of PNC-27 is directly superimposable on the structure for the same residues bound to HDM-2, suggesting that the peptide may target HDM-2 in the membranes of cancer cells. We now find significant levels of HDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 25 publications
6
39
0
Order By: Relevance
“…Also, there is a prominent red fluorescence in the membrane of these cells showing that HDM-2 is present in these membranes. Combined yellow fluorescence (green and red) is prominent, indicating that PNC-27 colocalizes with HDM-2 in the cancer cell membrane [79]. Very similar results were obtained using MIA-PaCa-2 human pancreatic cancer cells, MCF-7 human breast cancer cells [79] and a primary human ovarian cancer (E Yazdi, MR Pincus and J Michl, manuscript in preparation).…”
Section: Pnc-27 Binds To Hdm-2 Expressed Uniquely In Cancer Celsupporting
confidence: 69%
See 4 more Smart Citations
“…Also, there is a prominent red fluorescence in the membrane of these cells showing that HDM-2 is present in these membranes. Combined yellow fluorescence (green and red) is prominent, indicating that PNC-27 colocalizes with HDM-2 in the cancer cell membrane [79]. Very similar results were obtained using MIA-PaCa-2 human pancreatic cancer cells, MCF-7 human breast cancer cells [79] and a primary human ovarian cancer (E Yazdi, MR Pincus and J Michl, manuscript in preparation).…”
Section: Pnc-27 Binds To Hdm-2 Expressed Uniquely In Cancer Celsupporting
confidence: 69%
“…We have found that each of our structures for residues 17-26 of PNC-27 superimpose closely on the structure for the corresponding residues in the x-ray structure [79]. This superposition occurs despite the fact that the peptide in the x-ray structure is bound to MDM-2, and PNC-27 is present free in solution and the fact that the peptide in the x-ray structure contains three extra p53 residues while PNC-27 instead contains the MRP which the peptide in the x-ray structure does not contain.…”
Section: The Three-dimensional Structure Of Pnc-27 Shows That Itmentioning
confidence: 53%
See 3 more Smart Citations